The role of nickel catalyst in hydrogen desorption from MgH2: A DFT study. (10th August 2015) - Giusepponi, Simone; Celino, Massimo
Abstract: Magnesium hydride is a very promising material for solid-state hydrogen storage. However, some drawbacks have to be overcome to use it in real applications. The use of catalysts is a viable solution to lower the desorption temperature and increase the overall kinetics. An accurate model has been developed to study the mechanism of action of the catalyst and how it interacts with the interface MgH2 –Mg, through which H atoms diffuse. The accurate evaluation of the work of adhesion and defect energy formation, versus the distance from the interface are linked to the atomic-scale structural distortion induced by the catalyst. Moreover, molecular dynamics simulations at several temperature provide a clear description of the desorption mechanism and an estimate of the desorption temperature. Highlights: DFT numerical model for an MgH2 –Mg interface with Ni catalyst is set up. Extensive ab-initio molecular dynamics simulations of MgH2 –Mg interface are performed. Desorption temperature is estimated in excellent agreement with experimental results. Structural analysis reveals the catalytic role of Ni atoms. Catalysts and their interplay with interfaces are enlightened.